Subnational Regionalism in a Supranational Context: the Case of Hungary - David Ellison (Romanian Journal of European Affairs)
European economic integration drives a political economy of regionalism that—far more than traditional divisions between labor and capital—defines the principal axis of political-economic division in the New Europe. The New Economy drives a radical shift in EU policy from cohesion or redistribution toward innovation promotion, affecting distributional struggles and policy approaches at the EU, national and subnational levels. Shifting strategies pose significant challenges at the national and subnational levels with important implications for future EU, national and subnational economic and regional development policy goals. At the national level, and in particular less developed economies, the New Economy creates incentives for the increasing centralization of decision-making. EU-level reforms, such as the Lisbon Agenda and an increasing emphasis on cohesion as opposed to structural funding, do much to strengthen these trends. Subnational regions, at least in the near term, may be the principal losers. But such trends are likely to strengthen future demands for greater subnational political decentralization.